Unravelling the diversity in water usage among wild banana species in response to vapour pressure deficit - Eyland, David; Gambart, Clara; Swennen, Rony; Carpentier, Sebastien C. (Frontiers Media, 2023)
The rise in global temperature is not only affecting plant functioning directly, but is also increasing air vapour pressure deficit (VPD). The yield of banana is heavily affected by water deficit but so far breeding programs have never addressed the issue of water deficit caused by high VPD. A reduction in transpiration at high VPD has been suggested as a key drought tolerance breeding trait to avoid excessive water loss, hydraulic failure and to increase water use efficiency. In this study, stomatal and transpiration responses under increasing VPD at the leaf and whole-plant level of 8 wild banana (sub)species were evaluated, displaying significant differences in stomatal reactivity. Three different phenotypic groups were identified under increasing VPD. While (sub)species of group III maintained high transpiration rates under increasing VPD, M. acuminata ssp. e rrans (group I), M. acuminata ssp. zebrina (group II) and M. balbisiana (group II) showed the highest transpiration rate limitations to increasing VPD. In contrast to group I, group II only showed strong reductions at high VPD levels, limiting the cost of reduced photosynthesis and strongly increasing their water use efficiency. M. acuminata ssp. zebrina and M. balbisiana thus show the most favourable responses. This study provides a basis for the identification of potential parent material in gene banks for breeding future-proof bananas that cope better with lack of water.